Youth with Cerebral Palsy Display Abnormal Somatosensory Cortical Activity During a Haptic Exploration Task. (1st April 2023) - Trevarrow, Michael P.; Bergwell, Hannah E.; Groff, Boman R.; Wiesman, Alex I.; Wilson, Tony W.; Kurz, Max J.
Highlights: Individuals with cerebral palsy have reduced somatosensory cortical activity during movement. The reduced somatosensory cortical activity during movement is related to reduced somatosensory cortical activity during rest. The reduced somatosensory cortical activity during movement may contribute to clinical deficits in motor actions. Abstract: There are numerous clinical reports that youth with cerebral palsy (CP) have proprioceptive, stereognosis and tactile discrimination deficits. The growing consensus is that the altered perceptions in this population are attributable to aberrant somatosensory cortical activity seen during stimulus processing. It has been inferred from these results that youth with CP likely do not adequately process ongoing sensory feedback during motor performance. However, this conjecture has not been tested. Herein, we address this knowledge gap using magnetoencephalographic (MEG) brain imaging by applying electrical stimulation to the median nerve of youth with CP (N = 15, Age = 15.8 ± 0.83 yrs, Males = 12, MACS levels I-III) and neurotypical (NT) controls (N = 18, Age = 14.1 ± 2.4 yrs, Males = 9) while at rest (i.e., passive) and during a haptic exploration task. The results illustrated that the somatosensory cortical activity was reduced in the group with CP compared to controls during the passive and haptic conditions. Furthermore, the strength of the somatosensory cortical responses during the passive condition were positively associated with the strength of somatosensory cortical responses during the haptic condition (r = 0.75, P = 0.004). This indicates that the aberrant somatosensory cortical responses seen in youth with CP during rest are a good predictor of the extent of somatosensory cortical dysfunction during the performance of motor actions. These data provide novel evidence that aberrations in somatosensory cortical function in youth with CP likely contribute to the difficulties in sensorimotor integration and the ability to effectively plan and execute motor actions.